2014
DOI: 10.26687/archnet-ijar.v8i3.455
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical and Environmental Factors of a “Child Development Center” on a Center’s Selection

Abstract: The role of education is a key factor for an individual's development. After the 1980s the findings of educational research has shown that preschool age is a very important period in one's development. The single parent family structure and an increase in the number of working mothers have required children to attend schools in "child development centers" (CDC). Preschool education is becoming important in the new millennium because a child's personality, emotions, cognitive and social abilities develop during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our study found that children with visual impairment perform indoor activities, such as ADL, more easily than outdoor activities, likely due to the controlled and familiar indoor environment. Similarly, other studies have shown that the environment plays a significant role in the vision-related tasks of children with visual impairment, particularly when tasks involve senses other than vision, such as touch (Leffert and Jackson, 1998;Gur, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Our study found that children with visual impairment perform indoor activities, such as ADL, more easily than outdoor activities, likely due to the controlled and familiar indoor environment. Similarly, other studies have shown that the environment plays a significant role in the vision-related tasks of children with visual impairment, particularly when tasks involve senses other than vision, such as touch (Leffert and Jackson, 1998;Gur, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…It is necessary to know the physiological developments affecting the behavior of the child both directly and indirectly (Yavuzer, 2000). The socio-emotional development of the child in relation to his/her physical development is related to variables such as self-confidence, safety and comfort, interaction with the environment and definition of gender (Gur, 2014).…”
Section: Child Cognitive Development and Spatial Perceptionmentioning
confidence: 99%
“…Educational structures significantly affect students’ learning abilities, aspirations and motivation (Cole, 2011; Fisher and Dovey, 2016). In this context, the school enables the child to create different interactions in order to understand the child’s own self and to offer a social environment for interpersonal relations (Levin, 1980; Rubin, 1998; Gur, 2014). It is thought that the spatial experience of the child is important, as the educational buildings are the foremost places where this process develops.…”
Section: Primary School As a Physical Environment And Child’s Spatial Perceptionmentioning
confidence: 99%
“…Many governments and stakeholders around the world have put forward their focus on children's development, learning opportunities, and healthy living. Each country has preliminary school education regulations and has been a subject considered in a systematic education system [1]- [3]. Looking at the global scale, the UNESCO Incheon Declaration and Framework for Action 2030 underline the endeavour of Sustainable Development Goal (SDG) 4 for education to ensure that everyone has access to quality education, a safe learning environment and given a chance to learn throughout their lives.…”
Section: Introductionmentioning
confidence: 99%